Operational impact of RES penetration on a remote diesel-powered system in West Papua, Indonesia - Tuballa, Maria Lorena L. (2019)
When a new power source connects to the distribution or transmission grid, an assessment of its impact is necessary. Technical studies must assess the possible effects of a proposed expansion, reinforcement or modification to evaluate the possible incidents that may occur. Typically, the calculations or analyses done are load flow, short-circuit, and transient stability. The possible renewable energy (RE) sources are determined first. The details of the existing electrical system, including the specifications for the elements used, are obtained and logical assumptions are utilized for those that are not known. The load flow analysis in the considered case revealed that the RE presence reduces diesel generation. The 119 kW PV array and the 54 kW tidal turbine displace most diesel generation: 22% of Gen 4 and 21.8% of Gen 5. The diesel-solar system brought the diesel generation down by 20.05% of Gen 4 and 20% of Gen 5. The diesel-tidal combination lessened the diesel generation by 1.92% of Gen 4 and 1.83% of Gen 5. Short-circuit analysis alerts indicating the operating percentages of the circuit breakers that are beyond their interrupting ratings are presented. The transient stability analysis depicts that RE sources affect the existing system and appear to be putting in more stress. The studied systems are not transient-stable based on the results. While it is relatively simple to plan to put up renewables in remote island systems, there are many factors to consider such as the possible impacts of the RE sources.